Investigation of flexural and impact strength of carbon nanotube reinforced AA7075 metal matrix - Kasi V Rao, Pothamsetty; Raghu Kumar, B; Sudheer Kumar, B; Phanindra Swamy, G; Ganga Raju, Y; Sajjad Ali Khan, P (International Journal of Engineering and Technology, 2018)
Metal matrix nano-composites are grabbing more attention by many researchers in the recent years as they exhibit outstanding properties when compared to pure metal alloys. In the present study Aluminium Alloy 7075 was selected as the matrix and carbon nanotubes was selected as reinforcing element to investigate the percentage enhancement of flexural strength and impact strength of metal matrix composite. Stir casting process was selected to fabricate the specimens. The multi walled carbon nanotubes with different weight percentages (0.5, 1.0, 2.0, 5.0 wt %) were selected to prepare the AA7075-CNT metal matrix composite.Â Microstructure and dispersion of CNT was examined using Scanning Electron Microscope (SEM) with EDX. The experimental results of mechanical tests showed that if the MWCNTs particle content increases considerably flexural strength and impact strength also increases about 125% and 90% respectively. Thus the AA7075-CNT metal matrix can be used in automobile and aerospace applications under high load conditions.